The Polarization-Index: A simple calculation to distinguish polarized from non-polarized training intensity distributions - Treff, G.; Winkert, K.; Sareban, M.; Steinacker, J. M.; Sperlich, B. (Training intensity, volume and recovery Distribution among elite and recreational endurance athletes, 2019)
The training intensity distribution (TID) of endurance athletes has retrieved substantial scientific interest since it reflects a vital component of training prescription: (i) the intensity of exercise and its distribution over time are essential components for adaptation to endurance training and (ii) the training volume (at least for most endurance disciplines) is already near or at maximum, so optimization of training procedures including TID have become paramount for success. This paper aims to elaborate the polarizationindex (PI) which is calculated as log10(Zone 1/Zone 2 Zone 3 100), where Zones 1-3 refer to aggregated volume (time or distance) spent with low, mid, or high intensity training. PI allows to distinguish between non-polarized and polarized TID using a cutoff > 2.00 a.U. and to quantify the level of a polarized TID. Within this hypothesis paper, examples from the literature illustrating the usefulness of PI-calculation are discussed as well as its limitations. Further it is elucidated how the PI may contribute to a more precise definition of TID descriptors.